Mathematics Creative Thinking Skills in Creative Problem Solving Based on Cognitive Style - Yulianto, Hendra; Dwijanto, Dwijanto; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study was to describe students' mathematical creative thinking skills based on field independent and field dependent cognitive styles. The research uses mixed research methods with a concurrent embedded strategy. The population in this study were class VIII students of SMP Negeri 1 Sengah Temila in the academic year 2020/2021. The sample selection used cluster random sampling technique and obtained class VIII A as the experiment class and class VIII C as the control class. The final data analysis of the quantitative research used the right-hand average difference test and the normalized gain test. Final data analysis of qualitative research with data triangulation. The results showed that field independent students met the aspects of mathematical creative thinking skills. Field independent students are very interested in the new concepts learned, understand the given structure, good analytical skills and can work independently. Then the field dependent students also meet the aspects of mathematical creative thinking skills. Field dependent students are quite interested in the new concept being studied, do not understand the given structure, use an experiential approach to solving problems, and tend to require guidance and direction to solve problems.